From basic to fashion in the apparel industry: a study about upgrading in value chains - Pinto, Marcelo Machado Barbosa (2011)
This dissertation aims at explaining the elements involved with the upgrading processes in value chains. Empirical data about the upgrading processes of apparel production and consumption in Brazil is taken as a way to explore upgrading strategies in the context of a growing fashion industry. We assume that fashion has been a key element in the apparel production which responds to upgrading in apparel value chains, turning basic apparel into more valued products and services as they are embedded by particular social values recognized and legitimized as fashion trends. Consequently, fashion apparel is an enterprise which involves dealing with two different processes: (1) the tangible or material production process of apparel items and (2) the intangible or immaterial production process of fashion concept. To explain the two diverse but consonant processes, this study draws upon two theoretical approaches to unveil the value creation that leads to upgrading in apparel production. Both theoretical approaches feature value‐adding processes but in different ways: (i) the global apparel value chain industrial upgrading approach highlights the tangible production of apparel items through contractors industrial upgrading process and (ii) the fashion social embedded system approach focuses on intangible production of fashion concept or belief through a cultural upgrading process. Furthermore, bolstered on these two theoretical approaches and on empirical data, this study delineates three propositions to discuss and characterize the means by which upgrading occurs: (a) through a linear value chain configuration; (b) by way of a network system or (c) via 3 a loose chain. The results suggest that basic apparel production upgrades to fashion apparel production and consumption when different players intertwine, producing, sharing and/or incorporating intangible value‐adding activities such as designing and image‐making. The embedment of intangible value turns apparel players into hybrid forms casting doubt on the industrial/traditional upgrading approach of the apparel value chains. These hybrid forms reveal a broad perspective for upgrading in apparel production, highlighting a convergence of tangible and intangible activities related to apparel production in the realm of a fashion apparel loose chain.